Predictors for liver fibrosis in non-alcoholic patients with psoriatic diseases: A multicenter cross sectional-study. - Norberto Carlos Chavez-Tapia; Beatriz A Sanchez-Jimenez; Desiree Vidaña-Perez; Beatriz Corrales-Rosas; Brenda Balderas-Garces; Diana Vera-Izaguirre; Fermin Jurado Santa Cruz; Cesar Maldonado-Garcia; Eva Juarez-Hernandez; Misael Uribe (PLoS ONE)
Psoriasis has been related to metabolic dysfunction-associated fatty liver disease and, liver fibrosis. This study aimed to evaluate the prevalence of liver fibrosis in psoriasis and identify predictors for fibrosis. This is a cross-sectional study conducted from December 2012 to June 2016 assessing psoriasis and psoriatic arthritis patients attended at four centers in Mexico City. Data regarding history of the skin disease, previous and current medication, and previously diagnosed liver disease was collected. Liver fibrosis was assessed with four different non-invasive methods (FIB4, APRI, NAFLD score and elastography). We compared data based on the presence of fibrosis. Adjusted-logistic regression models were performed to estimate OR and 95% CI. A total of 160 patients were included. The prevalence of significant fibrosis using elastography was 25% (n = 40), and 7.5% (n = 12) for advanced fibrosis. Patients with fibrosis had higher prevalence of obesity (60% vs 30.8%, P = 0.04), type 2 diabetes (40% vs 27.5%, P = 0.003), gamma-glutamyl transpeptidase levels (70.8±84.4 vs. 40.1±39.2, P = 0.002), and lower platelets (210.7±58.9 vs. 242.8±49.7, P = 0.0009). Multivariate analysis showed that body mass index (OR1.11, 95%CI 1.02-1.21), type 2 diabetes (OR 3.44, 95%CI 1.2-9.88), and gamma-glutamyl transpeptidase (OR 1.01, 95%CI1-1.02) were associated with the presence of fibrosis. The use of methotrexate was not associated. Patients with psoriasis are at higher risk of fibrosis. Metabolic dysfunction, rather than solely the use of hepatotoxic drugs, likely plays a major role; it may be beneficial to consider elastography regardless of the treatment used. Metabolic factors should be assessed, and lifestyle modification should be encouraged.